MEASURING THE ROLE OF NON-PERFORMING FINANCING IN BOOSTING PROFITABILITY OF ISLAMIC COMMERCIAL BANKS - Lusy Pujiyanty; Rosana Eri Puspita; Mochlasin Mochlasin (Faculty of Economics Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
This study was conducted to analyze the effect of Murabahah financing, Capital Adequacy Ratio, and Financing to Deposit Ratio on Profitability with non-performing financing as moderating variables in Indonesian Sharia Commercial Banks. This research was conducted to prove the influence of the dependent and independent variables. The research method used in this study is quantitative. Data analysis in this study is multiple linear regression analysis. This study uses annual secondary data from islamic commercial banks from 2015 to 2019. The data is using an Eviews9 application. The study results after the classical assumption test showed that the variables of Murabahah financing, CAR, FDR, and non-performing financing passed the test. The test results show that partially Murabahah, CAR, and FDR financing variables have a positive and significant effect on ROA. Non-performing financing can weaken the impact of Murabahah, CAR, and FDR financing on ROA. The implication of this research is the result of this study can be used as an effort to increase and further strengthen their performance to minimize the occurrence of non-performing financing, which affects the profitability of the islamic commercial bank.